The Interactive Environment Architecture for Thermal-hydraulic Systems Simulation - Govorushchenko, Yuriy Nikolaevich (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2016)
The description of the principles of the multi-purpose graphical environment construction for thermal-hydraulic systems simulation is given. The functional capabilities of the specialized graphical editors for schemes and their components drawing are listed. The features of the software application for some subject areas, such as heat cycles of steam and gas turbines, turbomachinery flow paths, steam distribution nozzle systems, as well as hydraulic and pneumatic networks are presented. A brief comparison of the functionality of the developed programs with existing analogues is performed. It has been shown that the described architecture is particularly effective in combination with the use of object-oriented iteration-recursive algorithm for thermal-hydraulic systems simulation.